Diary of a wimpy kid; the ugly truth - Kinney,Jeff (Penguin, 2009)
For the adult readers of this book, it will make them feel nostalgic about their good old childhood days and help them recall how they struggled in the same way as Greg Heffley. So recall the reminiscent of your middle school age with 'Diary of a Wimpy kid: The ugly Truth’.